2001
DOI: 10.1002/j.2161-0045.2001.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

A Follow‐Up of Adult Career Counseling Clients of a University Extension Center

Abstract: An unannounced, telephone follow‐up evaluation of 181 out‐of‐school adults who had enrolled in 1 of 2 programs of individual career counseling at a university extension center indicated that 78% were satisfied or very satisfied. Eighty‐five percent reported that they were following through on their counseling in a variety of ways, including pursuing further education (35%) and changing jobs or occupations (14%). Satisfaction was not related at a statistically significant level to completion of their allotted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
3
13
0
2
Order By: Relevance
“…In general, the study highlights the value of having college counselors address the career needs of students. Previous research has validated the effectiveness of individual career counseling with college students (Healy, 2001). Findings from our study support the effectiveness of career interventions delivered as Journal of College Counseling Spring 2002 .…”
Section: Discussionsupporting
confidence: 75%
“…In general, the study highlights the value of having college counselors address the career needs of students. Previous research has validated the effectiveness of individual career counseling with college students (Healy, 2001). Findings from our study support the effectiveness of career interventions delivered as Journal of College Counseling Spring 2002 .…”
Section: Discussionsupporting
confidence: 75%
“…Although we evaluated the short‐term effects of an intervention, a follow‐up would be more instructive about the true value of career counseling (Morell, ). Researchers (Bernes et al, ; Healy, ) and organizations (Organisation for Economic Co‐operation and Development, ) advocate the use of follow‐up evaluation studies that investigate the short‐, medium‐, and long‐term effects of interventions (D. Hughes, Bosley, Bowes, & Bysshe, ) and the implementation of career plans (Phillips, ). The studies by Bernaud et al () and Perdrix et al () are examples of evaluation of career counseling using a follow‐up design.…”
Section: Discussionmentioning
confidence: 99%
“…Clients who underwent career counseling reported that they were overall satisfied with the process (Healy, 2001;Mau & Fernandes, 2001;Rochlen, et. al, 2004;Rochlen, et.…”
Section: Outcome Researchmentioning
confidence: 99%